Model Komunikasi Bisnis Jual Beli Buku Melalui Komunikasi Interpersonal dan Komunitas Grup Facebook - Iswahyu Pranawukir; Maria Jashinta Elisabet Hamboer (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
An online transaction activities are involving exchange of messages and information. This isactually part human activities in order to fulfill the human’s need which is also part of what socalledbusiness communication. Business communication itself has been improved and developedin many fields in recent years. Selling books online and using the social media platform such asFacebook is one of them. This study aims to study the business communication model of sellingbooks using particularly the social media platform of Facebook as a medium. In this context, thesellers play a role as the communicators while the buyers in the position of communicants.Throughboth method of non-participatory and participatory observations, this study shows there are threecategories of mainly books that sold online. First is the brand new books (new prints/new textbooks), second is the used books (known as the secondhand books) and the third is what so calledthe collectable, rare and antique books. Using an in-depth interview for analysing businesscommunication model and marketing strategies of selling books online in Facebook, it is evidencethat both sellers and buyers have been using and optimilising their networks of friendship throughtheir friend list contacts, both for their interpersonal as well as community communications. They utilise the communications among book lovers and book collectors as the most important strategyof their marketing approach. Therefore, it is clear that both personal and social networking areexisted side by side in this social media context for the purpose of their business communication.When someone selling a book online in Facebook, they normally would post the image or photodetailing the book which can be seen by all contacts in their networks including those book loversor book collectors who often would re-sell their book again online, by using the same social medianetworks. This research also shows that there are only certain kind of books that mostly soughtafter by people who use online book selling networks in Facebook. This information comes fromcontents mainly collected from the wall of Facebook. The list of most popular and top selling booksare quite long. Any works by the famous Indonesian writer Pramoedya Ananta Toer (PAT) are themost popular ones. People are also looking for books on literature, the leftist, military, history,religion, politics, economics, law, social and cultural issues. Leisure books such as comics andnovels are also selling well